Re-conceptualizing Techno-Linguistics: Using Technology for English Language Teaching? - Zhang, Xiaodong (International Journal of Emerging Technologies in Learning (iJET), 2019)
This short paper discusses the potential value of integrating linguistics theories with technological devices in English language teaching (ELT). In particular, the paper presents how systemic functional linguistics could be used to complement technology-based ELT. The paper ends with an innovative proposal of techno-linguistics (a term derived from the words technology and linguistics) as a research area to better benefit language learners in this digitalized world.